Reduced Serum Circulation of Cell-Free DNA Following Chemotherapy in Breast Cancer Patients - Evelyn Adusei; John Ahenkorah; Nii Armah Adu-Aryee; Kevin Kofi Adutwum-Ofosu; Emmanuel Ayitey Tagoe; Nii Koney-Kwaku Koney; Emmanuel Nkansah; Nii Ayite Aryee; Richard Michael Blay; Bismarck Afedo Hottor; Joe-Nat Clegg-Lamptey; Benjamin Arko-Boham (Medical Sciences, 2021)
Breast cancer is the most common malignancy in women, with alarming mortalities. Neoadjuvant treatments employ chemotherapy to shrink tumours to a well-defined size for a better surgical outcome. The current means of assessing effectiveness of chemotherapy management are imprecise. We previously showed that breast cancer patients have higher serum circulating cell-free DNA concentrations. cfDNA is degraded cellular DNA fragments released into the bloodstream. We further report on the utility of cfDNA in assessing the response to chemotherapy and its potential as a monitoring biomarker. A total of 32 newly diagnosed and treatment-naive female breast cancer patients and 32 healthy females as controls were included. Anthropometric, demographic and clinicopathological information of participants were recorded. Each participant donated 5 mL of venous blood from which sera were separated. Blood sampling was carried out before the commencement of chemotherapy (timepoint 1) and after the third cycle of chemotherapy (timepoint 2). qPCR was performed on the sera to quantify ALU 115 and 247 levels, and DNA integrity (ALU247/ALU115) was determined. ALU 115 and 247 levels were elevated in cancer patients but were significantly decreased after the third cycle of chemotherapy (T2) compared to T1. DNA integrity increased after the third cycle. Serum cfDNA may provide a relatively inexpensive and minimally invasive procedure to evaluate the response to chemotherapy in breast cancer.